Study of clinical characteristics of women with polycystic ovarian syndrome - Upadhya, Jeevanthy P.; Rai, Supriya; Acharya, Shrikrishna V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Polycystic ovarian syndrome (PCOS) is one of the most common endocrinal disorders of the reproductive age group causing anovulation, infertility incidence being 8.7-17.8%. It is associated with obesity, insulin resistance, dyslipidaemia and metabolic syndrome. This study was aimed to study the different clinical characteristics of women diagnosed with PCOS, attending a tertiary care hospital outpatient department. Methods: This was a hospital-based cross-sectional observational study of 200 patients with PCOS meeting the revised Rotterdam criteria from January 2018-June 2019 excluding pregnant and women with other systemic disorders. A detailed history and examination done, data collected regarding menstrual complaints, features of hyperandrogenism, hirsutism, acne, oily skin and Acanthosis Nigricans (AN) was documented. All data were statistically analyzed and compared using the chi-square or fissures’ exact test. p-value <0.05 considered significant. Results: A total of 200 patients with PCOS were included in the study, of which 41% were obese, 18% lean. The mean age was 24.44±5.62 years. Menstrual complaints were present in 88% -oligomenorrhea (49%) being the most common. 59% had hirsutism,38% of severe grade. Acanthosis nigricans was present in 33% of the patients. Correlation between hirsutism and alopecia, waist to hip ratio (WHR); acanthosis and WHR were statistically significant. Conclusions: PCOS is an ill-defined symptom complex where ethnicity plays a vital role, hence creating a greater need to know the characteristics of the syndrome in different populations and ethnicity. All women presenting with oligomenorrhea or other menstrual complaint should be investigated for PCOS and treated accordingly. The syndrome usually occurs with multiple characters. Though obesity is common in PCOS, non-obese are also at risk. The prevalence of AN and Hirsutism in PCOS were comparable. This mandates a need to increase awareness regarding the syndrome in the general population.